UMPSA students develop Cropfit Compost Maker to help mushroom farmers manage waste sustainably - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 11 August 2025 – The issue of the accumulation of old block waste in small oyster mushroom farms in Malaysia is becoming increasingly concerning, as most of this waste is either burned or left in open areas, which not only causes environmental pollution but also attracts pests that can disrupt farm operations.